The history of Belfast shipbuilding - Oldham, C.H. (Statistical and Social Inquiry Society of Ireland, 1912)
It is always interesting, and usually difficult, to explain why a great industry has taken root and prospered in one locality rather than in another. But in the case of the Belfast shipbuilding industry the explanation is simple enough. There we have a remarkable instance of the power of a dominant personality to create a new industry.
Read Tuesday, 20th December, 1910.
Keywords: Shipbuilding; Harland and Wolff; 314.15